Respuesta :
Answer:
[tex]\sf a^4 +16a^2 -b^2 a^2 -16b^2[/tex]
Explanation:
[tex]\sf ( a+ b) ( a- b) ( a^2 + 4^2)[/tex]
expand
[tex]\sf (a^2-ba+ba-b^2 ) ( a^2 + 16)[/tex]
simplify
[tex]\sf (a^2-b^2 ) ( a^2 + 16)[/tex]
expand
[tex]\sf a^4 +16a^2 -b^2 a^2 -16b^2[/tex]
Solution:
Note that:
- Given expression: (a + b)(a - b)(a² + 4²)
Formula: (a + b)(a - b) = a² - b²
Simplify the expression using the formula.
- (a + b)(a - b)(a² + 4²)
- => {(a + b)(a - b)}(a² + 4²)
- => (a² - b²)(a² + 16)
- => a⁴ + 16a² - a²b² - 16b²